Antioxidants and sports performance - Clemente-Suárez, V. J.; Bustamante-Sanchez, Á.; Mielgo-Ayuso, J.; Martínez-Guardado, I.; Martín-Rodríguez, A.; Tornero-Aguilera, J. F. (Nutrients, 2023)
The role of reactive oxygen species and antioxidant response in training adaptations and sports performance has been a large issue investigated in the last few years. The present review aims to analyze the role of reactive oxygen species and antioxidant response in sports performance. For this aim, the production of reactive oxygen species in physical activities, the effect of reactive oxygen species on sports performance, the relationship between reactive oxygen species and training adaptations, inflammation, and the microbiota, the effect of antioxidants on recovery and sports performance, and strategies to use antioxidants supplementations will be discussed. Finally, practical applications derived from this information are discussed. The reactive oxygen species (ROS) production during physical activity greatly influences sports performance. This review concludes that ROS play a critical role in the processes of training adaptation induced by resistance training through a reduction in inflammatory mediators and oxidative stress, as well as appropriate molecular signaling. Additionally, it has been established that micronutrients play an important role in counteracting free radicals, such as reactive oxygen species, which cause oxidative stress, and the effects of antioxidants on recovery, sports performance, and strategies for using antioxidant supplements, such as vitamin C, vitamin E, resveratrol, coenzyme Q10, selenium, and curcumin to enhance physical and mental well-being.